The role of probiotics in vaginal health - Mei, Zhaojun; Li, Dandan (Frontiers in Cellular and Infection Microbiology, 2022)
Probiotics have been widely used in the treatment of intestinal diseases, but the effect of probiotics on female reproductive tract health is still controversial. Lactobacillus is the most abundant microorganism in the vagina, which is related to the vaginal mucosal barrier. Lactobacillus adheres to the vaginal epithelium and can competitively antagonize the colonization of pathogens. The factors produced by Lactobacillus, such as bacteriocin and hydrogen peroxide (H2O2), can inhibit the growth of pathogenic microorganisms and maintain the low pH environment of the vagina. Probiotics play an important role in maintaining the stability of vaginal microenvironment, improving immune defense and blocking the progression of cervical cancer. We review the research progress of probiotics represented by Lactobacillus in gynecological diseases such as human papilloma virus (HPV) infection, bacterial vaginosis (BV) and Genitourinary Syndrome of Menopause (GSM), so as to provide basis for further exerting the role of probiotics in women's health.